A rapidly stabilizing water-gated field-effect transistor based on printed single-walled carbon nanotubes for biosensing applications - Molazemhosseini, Alireza; Viola, Fabrizio Antonio; Berger, Felix J.; Zorn, Nicolas; Zaumseil, Jana; Caironi, Mario (ACS applied electronic materials, 2021)
Biosensors are expected to revolutionize disease management through provision of low-cost diagnostic platforms for molecular and pathogenic detection with high sensitivity and short response time. In this context, there has been an everincreasing interest in using electrolyte-gated ﬁeld-eﬀect transistors (EG-FETs) for biosensing applications owing to their expanding potential of being employed for label-free detection of a broad range of biomarkers with high selectivity and sensitivity while operating at sub-volt working potentials. Although organic semiconductors have been widely utilized as the channel in EGFETs, primarily due to their compatibility with cost-eﬀective lowtemperature solution-processing fabrication techniques, alternative carbon-based platforms have the potential to provide similar advantages with improved electronic performances. Here, we propose the use of inkjet-printed polymer-wrapped monochiral singlewalled carbon nanotubes (s-SWCNTs) for the channel of EG-FETs in an aqueous environment. In particular, we show that our EGCNTFETs require only an hour of stabilization before producing a highly stable response suitable for biosensing, with a drastic time reduction with respect to the most exploited organic semiconductor for biosensors. As a proof-of-principle, we successfully employed our water-gated device to detect the well-known biotin−streptavidin binding event.
Gesehen am 04.09.2021